Neuromuscular and perceptual-cognitive response to 4v4 small-sided game in youth soccer players - Skala, F.; Zemková, E. (Frontiers in Physiology, 2023)
The physical and psychological load of small-sided games (SSGs) can affect players` neuromuscular and cognitive functions. Yet, little is known about the acute performance changes after such a specific exercise in young soccer players and their association with exercise load applied. This study investigates i) the neuromuscular and perceptual-cognitive response to the SSG exercise load, and ii) the relationship between pre- and post-SSG changes in variables of performance and the respective exercise load in youth soccer players. Sixteen participants (13.6 ± 0.5 years) underwent a 30-min SSG 4v4 + GK protocol. Prior to and after the SSG they performed countermovement jump (CMJ), planned and reactive Y-shaped agility tests (PA, RA), and go/no-go task (GNG). Their subjective perception of fatigue was evaluated by visual analog scale. Fatigue induced by SSG (perception of fatigue increased by 41.56%, p = .001, g = 4.15) increased PA time (4.04%, p = .002, g = .97), RA time (6.45%, p = .003, g = 1.16), and number of errors in the response inhibition task (87.1%, p = .023, rc = .57), whilst decreased CMJ height (-6.65%, p = .014, g = .56). These performance deteriorations were not significantly associated with neither internal nor external load variables. However, a less pronounced drop in performance was related to external load variables, i.e., DeltaCMJ height and DeltaRA time correlated with very high-speed running (rs = .66, p = .006; rs = -.50, p = .022; respectively) and maximal speed (r = .54, p = .032; r = -.52, p = .037; respectively), whilst DeltaPA time was associated with high-intensity accelerations (rs = -.76, p = .002). These findings indicate that fatigue induced by SSG affects both planned and reactive agility, decision-making in response inhibition task, and explosive strength in youth soccer players regardless of significant contribution of any robust internal or external load variables. Nonetheless, high-intensity actions within SSG partially compensate for the decrements in their agility performance and explosive strength. The load variables encountered during SSG do not fully reflect youth players` neuromuscular and perceptual-cognitive responses to sport-specific exercise.